Realizacja programu rozwoju małej retencji na obszarze województwa lubuskiego = Realization of the progress programme the small retention in the province lubuskie - Szpakowska, Marta; Warcholak, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
To improve the structure of water balance and to limit the economical losses which have occurred due to lack of water can begained by constructing the retentional abilities of river basin.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)